2020
DOI: 10.2174/1574887115666200519073704
|View full text |Cite
|
Sign up to set email alerts
|

Review on Recent Trials Evaluating the Effect of Intravitreal Injections of Anti-VEGF Agents on the Macular Perfusion of Diabetic Patients with Diabetic Macular Edema

Abstract: Background: Diabetic macular edema (DME) is a major cause of vision loss in diabetics worldwide. Anti-vascular endothelial growth factor (anti-VEGF) agents have become the mainstay of treatment of vision loss due to DME. Long-term effects of these agents on the macular perfusion (MP) are a current concern. Objective: To review recently published studies that evaluated the effect of intravitreal injection of anti-VEGF agents on the MP of diabetics with DME. Methods: Different databases were searched includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…28 Other studies have used OCTA to evaluate the effect of intravitreal injections of anti-VEGF agents on the FAZ size and VD measurements in the macula of patients with DME and yielded conflicting results, but these studies did not separately compare changes in responders and nonresponders. 17,20,[30][31][32][33][34] In the current study, we found a significant increase in the FAZ area in eyes that showed a reduction in CMT after three IVB injections, compared with those that did not respond to treatment (Supplementary Table S1). The differential change in vascularity between eyes that showed an early treatment response, versus those that did not, could be a cause or consequence of the different anatomical response of each group, which calls for further study in a larger number of eyes.…”
supporting
confidence: 57%
“…28 Other studies have used OCTA to evaluate the effect of intravitreal injections of anti-VEGF agents on the FAZ size and VD measurements in the macula of patients with DME and yielded conflicting results, but these studies did not separately compare changes in responders and nonresponders. 17,20,[30][31][32][33][34] In the current study, we found a significant increase in the FAZ area in eyes that showed a reduction in CMT after three IVB injections, compared with those that did not respond to treatment (Supplementary Table S1). The differential change in vascularity between eyes that showed an early treatment response, versus those that did not, could be a cause or consequence of the different anatomical response of each group, which calls for further study in a larger number of eyes.…”
supporting
confidence: 57%
“…Originally, this evaluation has depended on the use of FA and expert human graders [16][17][18][19][20][21][22], with several studies that later followed that employed ultra widefield FA imaging in order to evaluate the effect of these VEGF inhibitors on the peripheral retinal perfusion of diabetics as well [39,[47][48][49]. These studies, however, did not provide conclusive results regarding the effect of VEGF inhibition on the status of the macular perfusion of diabetic patients [50]. Prospective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in previous research, anti-VEGF drugs, such as bevacizumab, ranibizumab, aflibercept, and conbercept were effective for DME ( 14 , 29 ). However, there has been controversy about whether the macular perfusion will get better or worse after anti-VEGF treatment ( 15 , 22 24 , 30 ). Zhao et al considered that there were no significant changes of macular and papillary VD after either the panretinal photocoagulation or intravitreal conbercept treatment ( 23 ).…”
Section: Discussionmentioning
confidence: 99%